The effect of cold on performance and muscle damage during intensive training - Kapilevich, L. V.; Wang, Y.; Li, T.; Negodenko, E. S. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to assessing the effects of cold immersion on muscle damage and performance during intense training.